Computational investigation of potent inhibitors against YsxC: structure-based pharmacophore modeling, molecular docking, molecular dynamics, and binding free energy. Issue 3 (11th February 2023) - Kumari, Reena; Rathi, Ravi; Pathak, Seema R.; Dalal, Vikram
Abstract: In S. aureus, ribosome biogenesis GTP-binding (YsxC), a GTPase interacts with 50S subunit and 30S subunit of ribosome, and β' subunit of RNA polymerase and played an important role in protein synthesis. For the identification of potent lead molecules, we have conducted pharmacophore modeling by consideration of pharmacophore features of GTP among YsxC-GTP complex. Virtual screening and molecular docking results displayed that five pharmacokinetic and ADMET filtered molecules—ZINC000006424138, ZINC000095502032, ZINC000225415132, ZINC000095475800, and ZINC000012990761—had higher binding affinities than GTP with YsxC. All the identified molecules shared similar pharmacophore features of GTP and were stabilized via hydrogen bonds and hydrophobic interactions with YsxC. Molecular dynamics analysis revealed that YsxC-inhibitor(s) complexes were lesser dynamics and higher stable than YsxC-GTP complex. Molecular Mechanics/Poisson-Boltzmann Surface Area (MMPBSA) results confirmed that identified molecules bound at the active site (Arg33, Ser34, Asn35, Val36, Lys38, Ser39, Thr40, Thr54, Ser55, Pro58, Lys60, Thr61, Thr144, Lys145, Ser178, and Ile179) of YsxC and formed the lower energy (–190.32 ± 3.46 to –217.03 ± 2.55 kJ/mol) complexes than YsxC-GTP (–157.16 ± 2.89 kJ/mol) complex. The identified molecules in this study can be further tested and utilized to design novel antimicrobial agents for S. aureus . Communicated by Ramaswamy H. Sarma